How to obtain air quality permits - Greenway, A. Roger (McGraw-Hill, 2003)
Topics include: Introduction to Air Permitting; Assessing Compliance with Clean Air Requirements; Ambient-Air Quality Monitoring; Liabilities and Enforcement; State Permitting program; and State Environmental Agencies. CD-ROM included.